Energetics of the B-H transition in supercoiled DNA carrying d(CT)x.d(AG)x and d(C)n.d(G)n inserts. - Lyamichev, V I (1989)
We have studied the B-H transition in the d(AG)x inserts of varying length under superhelical stress. The new data and previously published results for the d(G)31 insert are treated within a phenomenological model of the B-H transition, making it possible to obtain, for the first time, the energy parameters of the B-H transition in the d(AG)x and d(G)n sequences.